Memaknai Kain Poleng Sebagai Inspirasi Penciptaan Karya Seni Lukis - Putra, I Kadek Sangging Adi Apreliana; Utami, Ni Made Purnami; Gulendra, I Wayan (PROGRAM STUDI SENI MURNI ISI DENPASAR, 2023)
The author's interest stems from the visual uniqueness of Poleng cloth which influenced the writer in adopting Poleng cloth as a painting. So it occurred to the author's desire to create a painting with the concept of Poleng Cloth as an inspiration for the creation of a painting that could represent the theme raised. The problem faced is how to visualize Poleng cloth to represent ideas, phenomena, meanings and techniques presented in creating works of art. The method of creation is a way of creating works of art systematically. In realizing this creation, the methods used are: the stages of exploration (exploration), imprivisation (experimentation), and forming (formation), which are supported by elements of fine art so that 6 works are created entitled: 1)